Design of Arabic Learning Based on the Merdeka Curriculum through PJBL for Islamic Senior High School - Ramadhanti Febriani, Suci; Bedra, Kddour Guettaoui (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The development of the Arabic language curriculum in Indonesia is increasingly complex. This is based on the increasing need for Arabic language skills in the international world. These basic needs are not only based on the ability to understand and read Islamic sources, but Arabic as an international language of communication is one of the demands of global skills. On that basis, this study aims to explore the design of learning Arabic based on the Merdeka Curriculum at the senior high school level using achievement indicators in the Merdeka Curriculum. The research technique is qualitative approach with data analysis based on content analysis. Data were obtained through literature study from the Merdeka Curriculum and other written sources such as books, articles and curriculum guideline. The results of the study indicate that the learning design based on PjBL (Project Based Learning) can implement the Merdeka Curriculum at the senior high school level. So, the demands of the 6 newest skills such as listening, speaking, viewing (memirsa), reading, writing and presenting can be organized in student projects. The research findings corroborate that the Arabic language learning system uses an Merdeka Curriculum to identify learning outcomes based on cognitive, affective and psychomotor competencies. The implications of this study identify that Arabic language learning needs to be practiced through various intensive assignment projects.